Does the Inion OTPSTM absorbable plating system induce higher foreign-body reaction than titanium implants? An experimental randomized comparative study in rabbits. (23rd September 2020) - Chalidis, Byron; Kitridis, Dimitrios; Savvidis, Panagiotis; Papalois, Apostolos; Givissis, Panagiotis
Abstract: Hardware removal after complete fracture healing is a laborious and traumatic procedure that bears the risks of refracture, infection, and soft tissue damage. Absorbable materials for fracture fixation have the advantage of eliminating the need for removal; however, they may stimulate a considerable inflammatory response. For that reason, we compared in a prospective randomized experimental animal model study the incidence of foreign-body reactions between Inion OTPS TM absorbable plate implants, consisting of carbon trimethylene, L-polylactic acid, and D, L-polylactic acid, and conventional titanium plates. Seventy rabbits were equally divided into two groups. Titanium (Group A) or absorbable (Group B) plates and screws were implanted in the femoral shaft of the rabbits. Wound reaction and laboratory tests including white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) values were measured and compared at different time points. Radiographs and histological analysis of tissue samples from all animals were also used to identify potential foreign-body reactions. WBC showed normal values in both groups. In Group A, ESR levels were higher at all time points but CRP values were normalized at 3 weeks postoperatively. In Group B, ESR and CRP levels reached a peak at 3 weeks and were above normal values throughout the whole experiment (p < 0.001). Radiologic examination revealed periosteal thickening and surrounding sclerosis in 23 out of 35 animals of Group B (66%). All Group A animals had normal radiographic findings. Histopathology showed a typical non-specific foreign-body reaction in all animals in Group B (100%) but none in Group A. However, only four of them (11.8%) developed non-infected wound complications and showed significantly elevated CRP and ESR values (p = 0.054). Although Inion OTPS TM Biodegradable Plating System stimulates a foreign-body reaction, only a small but not negligible percentage of almost 12% may lead to wound problems. However, this difference compared to titanium plates was of borderline not statistically significant. Future studies should focus on the development of absorbable implants with improved biocompatibility aiming to further decrease the potential of foreign-body reaction and eliminate the need for additional reoperative procedures.